Analisis Kebijakan Amerika Serikat Dalam Menangani Fenomena Human Trafficking dari Meksiko Periode Tahun 2010 – 2014 - Towafful Akbar Tofah; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Human trafficking was born as a form of modern slavery in this century. This crime is committed by traffickers using false promises and forms of coercion that force victims to work forcefully. In recent years, Mexico has been listed as a transit country and a supplier of trafficking victims. The United States is here as one of the countries that initiated the Antitrafficking policy. The Trafficking and Violence Protection Act of 2000 (TVPA) is a law made by the United States as an initial step to combat human trafficking. This thesis seeks to explain and analyze TVPA policy in Mexico-United States using Policy Theory and Concepts of National Interest with the aim of providing an understanding of the objectives of this TVPA policy. The analysis that was built sourced from sources in the form of reports, journals, books and other sources of literature that can support the writer's argument in this analysis. Based on data processed using selected theories, the United States built this policy as a security measure from the Mexican state that brought outbreaks of human trafficking to the United States and also to gain influence from other countries in combating human trafficking.